FORMING THE FOUNDATIONS OF CREATIVITY AND CONFIDENCE IN PRESCHOOL CHILDREN (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
This paper examines the crucial relationship between creativity development and confidence building in preschool-aged children, focusing on effective pedagogical approaches and methodologies. The research analyzes how creative activities and supportive educational environments contribute to developing self-confidence in early childhood. Through examination of current educational practices and developmental psychology principles, this study highlights key strategies for fostering both creative thinking and self-assurance in preschoolers. The findings emphasize the importance of integrated approaches that combine artistic expression, play-based learning, and positive reinforcement in early childhood education.